The Institute of the Scientific Atheism and the transformation of the field of religious studies in the USSR in the 1960–80s - Metel, Olga V. (Journal of the Belarusian State University. History, 2022)
This article examines the history of the opening of the Institute of Scientific Atheism of the Academy of Social Sciences under the Central Committee of the CPSU in the context of the transformation of Soviet religious studies in the mid 20th century. The author relies on a wide range of archival materials published and not previously introduced into scientific circulation. The author analyses the reasons for the emergence of the institution, examines the organisational units on the basis of which a new institution emerged. Close attention is paid to the reconstruction of the internal structure of the Institute of Scientific Atheism and its staff. Within the framework of the first of the named plots, the author studies both the evolution of problem groups of the institute and the peculiarities of the organisation of its regional branches, represented by support points and branches. Analysing the personnel structure of the Institute of Scientific Atheism, the author notes that its main feature is the active involvement of former party workers in the work of this center, who gradually acquired the necessary qualifications (in particular, candidate and doctoral dissertations). And although in the 1970–80s all employees of this center met the formal requirements for Soviet social scientists, the memory of the scientific community retained the names of only a few figures recognised as classics of Russian religious studies. Having reconstructed the main directions of research activities of the Institute of Scientific Atheism, the author comes to the conclusion that his employees were guided by the study of the most relevant and practically significant topics related to atheistic education or the religious situation in the modern world. That is why it was the activities of the Institute of Scientific Atheism that provided a significant narrowing of the research field of Soviet religious studies, which since the mid 1960s began to develop in the space of Soviet philosophy.
Keywords: the Institute of the Scientific Atheism of the Academy of Social Sciences under the Central Committee of the CPSU; the Soviet religious studies; the science of religions; the atheism